Pengelolaan Usaha Tiram Dalam Meningkatkan Ekonomi Keluarga Di Lajari Kabupaten Barru (Analisis Ekonomi Islam) - Nugroho, Muhammad Dandi; Muhammadun, Muzdalifah; Hamang, M. Nasri; Addury, Multazam Mansyur (Program Studi Ekonomi Syariah IAIN Parepare, 2022)
This research investigates the impact of oyster business management on improving the economic conditions of families in Lajari, Barru district, through the lens of Islamic economics. The study has three primary objectives: firstly, to assess the economic status of families in Lajari, Barru district; secondly, to analyze the contributing factors to the success of oyster business management in enhancing the family economy in the area; and thirdly, to explore the implementation of oyster business management in light of Islamic economic principles. Employing a qualitative research approach with a descriptive method, the study utilizes observation, interviews, and documentation as data collection techniques, drawing information from interviews with oyster business practitioners. The findings reveal several noteworthy aspects. First, the establishment of grilled oyster enterprises has positively impacted the economic conditions of families in the locality, leading to an indirect increase in their income. Second, the success of the grilled oyster business can be attributed to effective sales promotion, marketing strategies, and responsiveness to consumer demands, allowing the business to sustain and thrive over time. Third, oyster entrepreneurs exhibit appropriate business practices, prioritizing the common interests of the family without causing harm to others, and aligning their actions with Islamic principles in both income generation and management.